2013
DOI: 10.3126/jcmc.v3i1.8466
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Regarding Emergency Contraception Among Nursing Personnel

Abstract: Emergency contraception plays vital role reducing maternal mortality substantially and improves maternal health by avoiding unwanted pregnancy and unsafe abortion. The objective of this study was to find out the knowledge and attitude of nursing personnel regarding emergency contraception. On an average, 96.33% of nursing personnel had knowledge on general information of Emergency Contraception (EC), 88.78% had knowledge about intrauterine contraceptive device as EC, 66.1% had knowledge on general information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 4 publications
3
13
3
Order By: Relevance
“…Thapa in his study also reported that 78.18% of their participants had a positive attitude towards EC, 80% of their participants said that EC was safe for its users and 91.7% were ready to use EC personally whereas in our study 56.75% considered it as safe and only 47.56% were ready to use EC [7]. Similar to our findings no statistically significant difference between duration of experience and knowledge was noted [7].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thapa in his study also reported that 78.18% of their participants had a positive attitude towards EC, 80% of their participants said that EC was safe for its users and 91.7% were ready to use EC personally whereas in our study 56.75% considered it as safe and only 47.56% were ready to use EC [7]. Similar to our findings no statistically significant difference between duration of experience and knowledge was noted [7].…”
Section: Discussionsupporting
confidence: 85%
“…In our study 30.81% of the participants were aware that EC was available OTC but 74% in the above study had awareness about its availability [6]. In a study done in Nepal on nursing personnel 65.5% knew about the dosage and administration of EC and 88.78% were aware that IUCD can be used as EC [7].…”
Section: Discussionmentioning
confidence: 59%
“…26 Similar results were reported in other developing countries including India, Nepal, and south Africa. [27][28][29] In contrast to our finding high level of knowledge was reported among nursing student by a Brazilian study (86-96%) and in Iranian study (93.5%). 21,30 Most likely reason for this low knowledge among female health workers was that in nursing and midwifery curriculum, methods of contraception have been teaching superficially but neither providing formal training nor focusing the methods of emergency contraception.…”
Section: Discussioncontrasting
confidence: 55%
“…Data concerning provider knowledge was available in some studies [ 25 , 28 , 31 , 34 , 37 - 41 ]. While most providers surveyed felt ECP was safe [ 28 , 35 , 42 ] more than half of participants in some studies held reservations [ 30 , 34 , 37 , 41 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to prescription and/or dispensing were noted in a few studies, including low consumer demand [ 26 , 36 ], and ethical, legal and religious concerns of the providers [ 34 , 36 , 43 ]. ECP were regarded by some as delivering a cost saving to the health system through reducing the abortion rate [ 41 ] and unwanted child bearing [ 32 ], as well as an opportunity to promote regular contraception [ 47 ].…”
Section: Resultsmentioning
confidence: 99%